2004
DOI: 10.1007/s00198-004-1781-4
|View full text |Cite
|
Sign up to set email alerts
|

A triage strategy based on clinical risk factors for selecting elderly women for treatment or bone densitometry: the EPIDOS prospective study

Abstract: A triage strategy, based on a clinical hip fracture risk score, may be used to classify elderly women into three groups: one at high risk and requiring treatment, another needing further assessment by bone densitometry, and a third at low risk. We used prospective data from the EPIDOS study (7512 women older than 75 years and followed for an average of 3.9 years) to assess the potential value of such a strategy for identifying elderly women with a hip fracture risk twice the cohort average (i.e. > or =20 per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Age is considered to be one of the most important clinical risk factors for osteoporosis. 5,8 In this study the lamina dura and periodontal ligament were avoided during the selection of the ROI, although a recent study stated that there is no difference in the results when they are included. 28 Several authors have used self-administered questionnaires for assessment of osteoporosis based entirely on clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is considered to be one of the most important clinical risk factors for osteoporosis. 5,8 In this study the lamina dura and periodontal ligament were avoided during the selection of the ROI, although a recent study stated that there is no difference in the results when they are included. 28 Several authors have used self-administered questionnaires for assessment of osteoporosis based entirely on clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…4 Consequently, women are usually selected for bone densitometry based on clinical risk factors such as age, fracture history since menopause, low bone mass index and long-term corticosteroid use. [5][6][7][8][9][10][11][12] It is well known that osteoporosis results in the alteration of the mandibular structures, especially the mandibular cortex. [13][14][15][16][17][18][19][20][21][22][23] Recent studies have linked osteoporosis to alterations of the trabecular bone, visible in dental radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…In a large cohort, a total of 7.512 women older than 75 years which were followed for an average of 3.9 years in the prospective epidemiology of OP study. This study revealed that fracture history since the age of 40 years was one of the most valuable predictors of hip fracture (20). Although in some studies delayed menarche, premature menopause, and short reproductive period were reported as possible risk factors, other studies found no association (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 78%
“…One approach is to select individuals older than 65 years. The rationale is that there is an exponential rise in the risk of fractures with age [22], and older individuals may be more amenable to treatment. The major advantage of screening in later life is to increase the proportion of individuals identified who will sustain fractures and be targeted for treatment.…”
Section: Screening Later In Lifementioning
confidence: 99%